Surface morphology features of point contact gas sensors based on Cu-TCNQ compound. Issue 1 (24th March 2021) - Harbuz, D. A.; Pospelov, A. P.; Gudimenko, V. A.; Konotop, A. P.; Mateychenko, P. V.; Kowalska, D. A.; Faulques, E.; Kamarchuk, G.V.
Abstract: The 7, 7, 8, 8-tetracyanoquinodimethane (TCNQ) radical anion salt compound was used as the sensitive material of gas point contact sensors. The phase composition and surface morphology of the obtained sensor films were established. It was found correlation between surface morphology of the point-contact transducer and definite type of the sensor response curve observed under action of the human breath gas. If the sensor sample is formed from numerical crystals of the same or similar sizes having a uniform shape, similar to a shell, and clearly defined external borders it indicates to the creation of defect-free Yanson point contacts in the process of soft electrochemical synthesis. As a result, the surface of the sensor is a complex multistructure of a numerous number of Yanson point contacts, which generates a large output signal from the sensor in response to the action of the analyte. When crystals of Cu-TCNQ compound forming samples under investigation have lower density, large size, distorted and full of fractures boundaries, it prevents the formation of high-quality point contacts. These morphologic peculiarities are typical for samples with low level of response signal. In the case of extremely low density of Cu-TCNQ crystals observed in the sample surface the sample does not show any response to the action of the human breath gas.